Analysis of photovoltaic technology development based on technology life cycle approach - Jamali, Mahdis Yousef; Aslani, Alireza; Moghadam, Babak Farhang; Naaranoja, Marja; Madvar, Mohammad Dehghani (AIP Publishing, 2016)
Increasing energy demand has created the challenge of supplying safe, economical, and durable energy with minimal impact on the environment. Therefore, governments have developed and executed several strategies such as increasing efficiency in energy systems in addition to replacing existing sources with renewable energies. One of the most important renewable energy sources that have a competitive advantage compared with other resources is solar energy and its related technologies. However, development of this technology, its related products, and their competitiveness in the market has created a plethora of challenges. In this study, the focus is on the analysis of photovoltaic technology development in the context of different technology generations. The S-shape curve of each generation and sub-technologies of photovoltaic is designed and analyzed. Results show that the first generation of photovoltaic technology is in growth and early maturity stage. The second generation is also in growth stage, but the third generation is mainly in the introduction stage.
Keywords: Renewable energy; Chemical elements; Fossil fuels; Semiconductor materials; Photovoltaics; Solar energy; Energy system; Solar cells; Energy technology; Transition metals; fi=Tuotantotalous|en=Industrial Management|